2020
DOI: 10.1136/bmj.m3808
|View full text |Cite
|
Sign up to set email alerts
|

Making pharmaceutical research and regulation work for women

Abstract: The legacy of male bias within pharmaceutical research, regulation, and commercialisation needs to be rectified, argue Sundari Ravindran and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
(80 reference statements)
0
31
0
Order By: Relevance
“…Sex factors, including sex-disaggregated analysis and reporting, are still neglected across the continuum of medicines research and regulation. 7 This is also the case in COVID-19 trial data reporting. According to an evaluation in preprint 8 of nearly 2500 COVID-19-related studies, less than 5% of investigators had pre-planned for sex-disaggregated data analysis in their studies.…”
mentioning
confidence: 81%
“…Sex factors, including sex-disaggregated analysis and reporting, are still neglected across the continuum of medicines research and regulation. 7 This is also the case in COVID-19 trial data reporting. According to an evaluation in preprint 8 of nearly 2500 COVID-19-related studies, less than 5% of investigators had pre-planned for sex-disaggregated data analysis in their studies.…”
mentioning
confidence: 81%
“…Drawing from parallel regulatory levers, the establishment of national requirements for local data in countries such as in Japan, India and China drove the conduct of clinical trials in these countries. 17 The implementation of internationally adopted guidelines and standards for the evaluation and regulation of pediatric products, and national incentives facilitated the pursuit of formal indications and better data in children. 18 In the case of sex and gender considerations, the ICH should consider revisiting a 16-year old assessment that specific guidelines are not necessary on how sex should be included, and reported in studies, through an updated review on the role of sex factors across disease areas, and gaps in guideline recommendations, implementation and enforcement in global product evaluations and standardized regulatory dossiers.…”
Section: Holding ‘Feet To Fire’: Establishing and Enforcing Regulator...mentioning
confidence: 99%
“…We also need more women in decision-making positions in R&D, regulatory and industry leadership. 6 , 17 However, tokenistic representation is not enough. Systemic change is required.…”
Section: Aligning Call To Parallel Conversations On Intersectionality...mentioning
confidence: 99%
“…We now have the opportunity to course-correct the integration of biological sex as a core variable in research reporting, design, and analysis because sex factors (sex-disaggregated analysis and reporting) are being ignored globally during the era of COVID-19 vaccine innovative research and regulation [ 27 ] as well as in COVID-19 trial data reporting (8 from lancet). A review of approximately 2,500 COVID-19-related studies revealed that less than 5% of researcher/investigators had intended for sex-disaggregated data analysis in their research [ 28 ].…”
Section: Covid-19 Vaccine Trials and Sex-disaggregated Datamentioning
confidence: 99%